2021
DOI: 10.1002/adfm.202107285
|View full text |Cite
|
Sign up to set email alerts
|

Tough Carbon Nanotube‐Implanted Bioinspired Three‐Dimensional Electrical Adhesive for Isotropically Stretchable Water‐Repellent Bioelectronics

Abstract: Integrated bioelectronics with conformal adhesion interfaces on dry/wet biosurfaces and water‐repellent stretchable electric elements are in high demand for reliable real‐time diagnostics of the dynamic human body. Here, the authors present a diving beetle‐inspired electro‐adhesive patch with mechanically robust nanowire‐implanted conductive multiscale architectures that provides a skin‐adaptable, isotropically stretchable interface for a multiple‐biosignal monitoring device. Using a facile all‐solution‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…It is directly mounted onto the wrist or instep of a healthy volunteer, where the arteries are superficial and the pulse waveforms are palpable, through a biocompatible adhesive, which could be replaced by novel underwater adhesives with longterm stability and biosecurity. [54] Figure 5b summarizes tactile measurements of the arterial pulse waveforms by the aquatic skin before and after underwater exercise. An increased heart rate has been observed from 72 to 110 BPM, accompanied with a substantially elevated pulse magnitude of the skin pressure from 1.0 to 2.4 kPa, accordingly.…”
Section: Aquatic Skin For Monitoring Of Vital Signs and Environmental...mentioning
confidence: 99%
“…It is directly mounted onto the wrist or instep of a healthy volunteer, where the arteries are superficial and the pulse waveforms are palpable, through a biocompatible adhesive, which could be replaced by novel underwater adhesives with longterm stability and biosecurity. [54] Figure 5b summarizes tactile measurements of the arterial pulse waveforms by the aquatic skin before and after underwater exercise. An increased heart rate has been observed from 72 to 110 BPM, accompanied with a substantially elevated pulse magnitude of the skin pressure from 1.0 to 2.4 kPa, accordingly.…”
Section: Aquatic Skin For Monitoring Of Vital Signs and Environmental...mentioning
confidence: 99%
“…application of bioinspired CNT-based materials in nanopatterned surfaces. 132,133 Liz-Marza ´n et al reported classical sea-anemonelike CNT-based hollow capsules with magnetic and reinforced properties. The CNT-coated Fe 3 O 4 NP@PS spheres were used as the ''hair'' to provide the reinforcement.…”
Section: Nanopatterned Surfacesmentioning
confidence: 99%
“…Besides their potential as reinforcing materials with high mechanical strength and chemical stability, the unique nanoscale morphology, low hydrophilicity, and optical characteristics of assembled structures of CNTs are also instructive for the application of bioinspired CNT-based materials in nanopatterned surfaces. 132,133 Liz-Marzán et al reported classical sea-anemone-like CNT-based hollow capsules with magnetic and reinforced properties. The CNT-coated Fe 3 O 4 NP@PS spheres were used as the “hair” to provide the reinforcement.…”
Section: Applicationsmentioning
confidence: 99%
“…Bio-inspired surfaces having specific wet-adhesive properties are already used in a variety of application fields (Ahn 2017;Baik et al, 2019;Chen et al 2018aChen et al , 2018bChen et al , 2019Liu et al, 2021;Wang et al 2018aWang et al , 2020bWang and Hensel 2021). For example, they can be employed as portable drug delivery patches for eye treatment (Than et al, 2018;Yang et al, 2013) and micromotors for stomach care (Cai et al, 2022), wearable flexible devices for the monitoring of physiological conditions of humans (Chun et al, 2018;Kim et al 2019Kim et al , 2021Lee et al, 2021;Min et al, 2021), and as medical tapes for wound treatment (Chen and Yang 2017;Peng et al, 2021) and skin care (Baik et al, 2021). They can be also used as the adhesive pads for bionic robots, as adhesive devices for the transport of liquid droplets in intelligent manufacturing (Chen et al, 2018b;Li et al, 2020), as wet adhesives for the repair of pipes and as smart tapes for micro/nanofilm transfer (Figure 2) (Lee et al, 2016;Park et al, 2021;Yi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%